Numerical Analisys of Segmental Box Girder’s Stress with Eccentric Tendon Anchoring on Balanced Cantilever Box Girder Bridge - Kevin Raenaldo; M. Sigit Darmawan; Nur Ahmad Husin (Institut Teknologi Sepuluh Nopember, 2025)
Diagonal crack damage on the web of balanced cantilever box girder bridges has frequently occurred worldwide, including in Indonesia. Previous studies have shown that these cracks can result from additional shear stress caused by prestressed tendon anchoring. In this study, an analysis was conducted using a 2D element model verified through a numerical approach. The evaluation of box girder web stress values was used to assess the potential for cracking and confirm the results of crack mapping conducted on site. The research found that shear stress from prestressed tendon anchoring increases the total shear stress on the box girder web by up to 46.6% of the total shear stress value. The distribution of shear stress from prestressed tendon anchoring is concentrated in the anchoring areas on the top slab and bottom slab sides of the box girder web. The evaluation of principal tensile stress shows that the observed crack locations in the field correspond to areas where the principal tensile stress values exceed the allowable design limit.